The edge of nowhere [large type] - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Onion Creek series, 2024)
"Ridge Tisdale is a haunted man. After losing his family in a brutal Comanche raid, he drifts from town to town seeking justice and revenge. His mission -- to track down the killers -- has hardened his heart against all men, good or bad. But his icy resolve begins to melt when he arrives in the small Texas town of Blackjack -- along with a massive winter storm that traps him there with a good woman, her little girl, and some very bad men . . . Texans call it a Blue Norther. A fast-moving onslaught of heavy sleet and snow, it brings Tisdale's search to a halt, but also gives him a chance to warm up with the charming young widow who runs the general store. Her name is Maggie McBrayer. She has a friendly smile, a five-year-old daughter -- and a terrible problem with mean-spirited cowboys stealing supplies from her store. Being a gentleman, Foley raises his gun to defend the widow and stop the thieving snakes. But the battle is far from over . . . The storm is getting worse. The cowboy gang is snowbound, too -- and they're ready for a rematch. If Tisdale, the widow, and her daughter can survive the night, it'll be a Christmas miracle . . ."--